(untitled) (Bangladesh Journal of Botany, 2025)
Hedlundia caucasica (Zinserl.) Mezhenskyj previously placed as a synonym of H. armeniaca (Zinserl.) Mezhenskyj. Both species exhibit a distribution in closely related areas and are morphologically characterized by red and fleshy fruits, lobed leaves, and numerous flowers. However, these two Hedlundia species are sister group in phylogenetic analyses, and it has been determined that they do not share similar gene sequences in chloroplast (trnK-rps16) and nuclear (ITS) DNA gene regions analysis. Additionally, H. caucasica differs from H. armeniaca by its leaf sizes, leaf vein, leaf shape, number of leaf lobes, leaf apex, tomentose hairs below leaf and the structure and number of leaf teeth. Based on the result of the analyses, it has been determined that these two species differ morphologically and molecularly, and therefore, Hedlundia caucasica is considered a separate taxonomic species. Bangladesh J. Bot. 54(2): 301-309, 2025 (June)